The role of potential staying duration of the cells in peripheral blood - V. V. Svischenko; N. A. Stakhin (Бюллетень сибирской медицины, 2007)
For evaluation of potential staying duration of cells in peripheral blood on the character of cell kinetics, method of mathemati-cal modeling was used. Potential staying duration of cells in peripheral blood was numerically shown to deeply influence on anemia, but only for the small share of cells' death.